Estudio Comparativo de las Tecnologías de Software y Hardware que permitan la comunicación con personas autistas. - Choez Caice, Joselyn Raquel (2018)
The changes produced by new information technologies (ICTs) are present in all areas of our lives and, therefore, it is a major benefit to expand knowledge about how the brain works and even improve the quality of life of children with Autism Spectrum Disorders (ASD). For which it would be feasible that ICTs can give parents an option to improve the way they interact with children who suffer from autism disorder because the learning difficulties are very notorious in this social field. ICTs can be a very useful tool to help children with ASD, since that this is a developmental disability that can cause social problems, communication or behavior, usually there are no differences towards other people, it is It is possible for people with this disorder to interact with other people in a way that different What you can do is find methods to communicate with them and improve their lifestyle, this research seeks to describe the improvements children can make Autistic people using ICTs as learning tools. The work will be structured as follows, historical description of the Autism, current research on ICT applications of this type of disorder, collecting information from some authors, selecting appropriate applications for these children with ASD, with a small explanation of each and make comparison of software and Useful hardware for people with autism.